PENERAPAN ILMU EKONOMI DALAM PENGELOLAAN LINGKUNGAN HIDUP DAN PENGENDALIAN PENCEMARAN LINGKUNGAN - Mariyono, Joko (LPPM Universitas Terbuka, 2006)
Environmental pollution is inevitably caused by economic activities. However, the pollution can be controlled to obtain optimal pollution that provides maximum net benefit of the economic activities. Indentification of the polluters is needed when the optimal pollution is determined. Economic instruments can be used to insist the polluters to control their economic activities. Selection of economic instruments that will be applied will work properly if the value of environmental pollution is well known. In fact, the pollution is not marketable, and therefore, economic valuation of the pollution is required. Some techniques of valuation have been introduced, based on the types of pollution. Shortly speaking, economics can be applied in controlling pollution resulting from economic activities.